The Sudbury Basin stress tensor – myth or reality? - Suorineni, F.T.; Malek, F. (Deep Mining 2014: Proceedings of the Seventh International Conference on Deep and High Stress Mining, 2014)
Sudbury Basin is host to many underground mines, most of which are seismically active. Some of these mines, e.g. Creighton Mine, have been in operation for over a century and can be said to be matured. Others, e.g. Glencore Xstrata Nickel Rim South Mine, have just been opened and can be classified as young. Several in situ stress measurements have been performed in these mines over the years. Mine seismicity and rockburst research has been very active in the Sudbury Basin since 1984 following the then Falconbridge Mine disaster. Stress tensor is one of the critical inputs in numerical models for the assessment of excavation performance, support demand and rockbursts and seismicity potential. It is also an important input in closed-form solutions for similar purposes. Over the years, several technical reports have referred to a Sudbury Basin stress tensor. In a recent review study of stress measurements in the Sudbury Basin as a means of validating the so called Sudbury Basin stress tensor, the supposed stress tensor source could be hardly identified. It is important to recognise that in situ stress measurement errors remain significantly high and would be unacceptable in any other branch of engineering (Hoek 1994). To improve confidence in these measurements several carefully measured data are required. For this reason the Sudbury Basin stress tensor if it existed would have had to be updated with the addition of the several stress measurements in the Basin in recent times following its development. Strangely, this is hardly the case. The paper draws the attention of rock engineers to the myth of the Sudbury Basin stress tensor. Based on review of available Vale stress measurement database and interviews of past prominent ground control engineers who have worked in the Basin, including Phil Oliver (pers. comm.) and Dr G Swan (pers. comm.) suggests a plausible, generic, Sudbury Basin stress tensor. The developed stress tensor compares very favourably with what is known from experience in the Basin. The authors give credit to Vale for its continuing effort in stress measurements within the Basin.